2019
DOI: 10.1097/brs.0000000000002961
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Spinal Magnetic Resonance Imaging Findings in Asymptomatic Young Adults (18–22 Yrs) Candidate to Air Force Flight

Abstract: Study Design. Cross-sectional, retrospective, magnetic resonance (MR) imaging study, performed during cadets’ selection procedures of the Italian Air Force Academy. Objective. To assess the prevalence of spinal MR imaging findings in asymptomatic young adults (18–22 yrs) candidate to Air Force Flight. Summary of Background Data. Spinal MR imaging findings are frequently detected in asymptomatic subjects. Lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
1
4
1
3
Order By: Relevance
“…At the level of the lumbar spine, nearly 39% of the lumbar discs demonstrated some degree of degeneration with two thirds of them classified as mild and one third as moderate or severe degeneration. Although lumbar disc degeneration is a common imaging finding in asymptomatic and symptomatic young individuals, our study showed that Olympic athletes have higher prevalence of moderate to severe disc degeneration than nonathletes [14,[29][30][31]. Even with the wide variation related to sample sizes, different age ranges, different clinical presentation, and different criteria and classification of the degenerative changes, our results are in accordance with several prior studies that showed the higher rate of these degenerative changes of the lumbar spine in athletes [1,2,6,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…At the level of the lumbar spine, nearly 39% of the lumbar discs demonstrated some degree of degeneration with two thirds of them classified as mild and one third as moderate or severe degeneration. Although lumbar disc degeneration is a common imaging finding in asymptomatic and symptomatic young individuals, our study showed that Olympic athletes have higher prevalence of moderate to severe disc degeneration than nonathletes [14,[29][30][31]. Even with the wide variation related to sample sizes, different age ranges, different clinical presentation, and different criteria and classification of the degenerative changes, our results are in accordance with several prior studies that showed the higher rate of these degenerative changes of the lumbar spine in athletes [1,2,6,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…None of the participants presented disc extrusion. Romeo [24] reported that the prevalence of disc protrusion, and extrusion in spine were 18% and 8% in candidates to the air force, and the results were higher than that in our study (14.6% and 0%). One possible explanation was that the participants were all candidates to the air force in Romeo study, while in present research those failing to meet the selection criteria of aviators were excluded at the very beginning of selection process, as obvious disc herniation was one exclusion criterion.…”
Section: Discussioncontrasting
confidence: 87%
“…While conventional medical imaging (radiographs, computed tomography, and magnetic resonance imaging (MRI)) can provide excellent visualization of the spatial relationship between the neural structures and the spinal anatomy, the predictive value of conventional imaging for spinal disease is limited. Incidental findings of degeneration, disc pathology, and spinal nerve root compromise, as well as spinal cord compression, are present with high prevalence in asymptomatic individuals ( Brinjikji et al, 2015 ; Romeo et al, 2019 ), and the increased use of medical imaging has not necessarily led to meaningful improvements in clinical outcomes ( Deyo et al, 2009 ; Maus, 2010 ). More sensitive measures of nervous system pathology are needed to better identify and localize the clinically significant spinal pathology to improve the clinical management of the spine.…”
Section: Introductionmentioning
confidence: 99%